A self-powered tunable unipolar synchronized electric charge extraction interface circuit for piezoelectric energy harvesting. (March 2023) - Jia, Shengyao; Zeng, Chuanjun; Shi, Ge; Tong, Dike; Li, Qing; Xia, Huakang; Xia, Yinshui
In this work, a self-powered tunable unipolar synchronized electric charge extraction (STU-SECE) interface circuit is proposed to harvest the maximum available power from the piezoelectric transducer which meets the condition of strong enough coupling ( k 2 Q ≥ π/2). It reveals the constraint equations about the parameters of modified electromechanical coupling coefficient, vibration angular frequency and tuning parameter should satisfy when STU-SECE harvests the maximum available power, and demonstrates how to use resistances to set the tuning parameter to control the charge extraction phase of the circuit. Simulation results show that STU-SECE can basically achieve the theoretical optimum in harvested power from the transducer. Experimental results show that the maximum harvested and output power of STU-SECE are increased by 11% and 7% compared to unipolar synchronized electric charge extraction (U-SECE), and are increased by 108% and 157% compared to SECE under the same conditions, which verify the effectiveness of the proposed STU-SECE circuit and the constraint equations.